The collection of test tasks on hospital pediatrics on outclass preparation for 6-th grade English-speaking students of medical faculty - Lezhenko, G. O.; Reznichenko, J. G.; Pashkova, О. E.; Kamenshchyk, А. V.; Vrublevska, S. V.; Lebedinets, О. М.; Леженко, Геннадій Олександрович; Резніченко, Юрій Григорович; Пашкова, Олена Єгорівна; Каменщик, Андрій Володимирович; Врублевська, Світлана Володимирівна; Лебединець, Олександра Миколаївна (Zaporizhzhya state medical university, 2014)
The important section for the 6-th year students education is the mastering of practical skills on neonatology, children hematology, children endocrinology, pulmonology, cardiology, gastroenterology, nephrology which are necessary for solving the problems in diagnostics, differential diagnostics, treatment and prophylaxis of above mentioned pathology in children. The student master these skills during all types of studying in hospital pediatrics course. The student ought to see any diagnostic or treatment method in action, to know the ptrinciples of it, ought to complete it in certain clinical situation, to clarify the obtained results of diagnostic tests or the treatment.
Збірник тестових завдань з госпітальної педіатрії для самостійної роботи англомовних студентів